ANALISIS PERSEPSI PEREMPUAN GEN Z TERHADAP TREN “MARRIAGE IS SCARY” DALAM PERSPEKTIF MAQASID SYARIAH (STUDI KASUS MAHASISWI UIN RADEN MAS SAID SURAKARTA) - lutfiyah hidayati; Sulhani Hermawan (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The trend of “Marriage is Scary” among Generation Z women reflects a changing perspective on marriage. Many young women feel afraid to marry due to concerns about conflict, domestic violence, economic challenges, and the loss of personal freedom. This study aims to understand the perceptions of Gen Z women toward the “Marriage is Scary” trend and to examine them through the perspective of Maqasid Syariah. This research uses a qualitative descriptive method involving ten Muslim female respondents aged 18–25 years. The findings show that social media, family experiences, and economic conditions are the main factors that shape fear toward marriage. From the perspective of Maqasid Syariah, marriage is an act of worship aimed at preserving religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-aql), lineage (hifz al-nasl), and wealth (hifz al-mal). Therefore, strengthening religious literacy, mental readiness, and financial preparation is essential so that the young generation can view marriage as a path to peace, happiness, and overall well-being.